Conductive paste for solar cells

By using vinyl silicone oil and polymerization inhibitors in the conductive silver paste, the problems of gate line width widening and cell efficiency reduction caused by organic components decomposition during sintering and drying in the prior art are solved, and a higher aspect ratio and higher photovoltaic conversion efficiency are achieved.

CN113871052BActive Publication Date: 2025-03-14SHANGHAI SILVER PASTE SCI & TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202110757449.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-07-05
Publication Date
2025-03-14
Estimated Expiration
2041-07-05

AI Technical Summary

Technical Problem

During the sintering and drying process of the existing conductive silver paste used in silicon solar cells, the gate line width widening and battery efficiency decreases due to the decomposition of the organic components.

Method used

Using a conductive paste containing vinyl silicone oil and a polymerization inhibitor, the vinyl silicone oil inhibits the linear collapse of the gate line during the polymerization reaction, and its stability at room temperature is improved by the polymerization inhibitor.

Benefits of technology

The stability and aspect ratio of the slurry during drying or sintering are achieved, thereby narrowing the gate line width and improving the short circuit current and photovoltaic conversion efficiency of the solar cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113871052B_ABST
    Figure CN113871052B_ABST
Patent Text Reader

Abstract

The present invention discloses a conductive paste for solar cells, comprising conductive metal powder, glass powder, and an organic carrier; wherein the organic carrier comprises a thermoplastic polymer, vinyl silicone oil, a polymerization inhibitor, other organic additives, and an organic solvent. By using vinyl silicone oil instead of traditional silicone oil and adding a proper amount of polymerization inhibitor, the photovoltaic conversion efficiency of the solar cell can be improved by increasing the height-to-width ratio of the grid lines formed and reducing the undulation of the grid lines, and the stability of the conductive silver paste can also be maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of photovoltaic technology, and in particular to a conductive paste for solar cells. Background Art

[0002] The photovoltaic industry is booming, and silicon solar cells currently occupy more than 80% of the market. The electrode grid lines for the light-receiving surface of silicon solar cells are formed by screen printing, drying and sintering of conductive paste. Therefore, the electrode grid lines should be as narrow as possible and have a good aspect ratio, so as to reduce the reduction in photovoltaic conversion efficiency caused by the shielding of incident light. The conductive silver paste used for silicon solar cells is generally composed of an organic carrier, glass powder and conductive metal powder. The carrier part of the conductive paste usually contains silicone oil. The silicone oil in the paste plays a role in adjusting the viscosity of the paste, improving the mesh passing property of the paste, leveling and better aspect ratio. However, during the sintering and drying process of the paste, the organic components in the paste including silicone oil will decompose due to heating, resulting in the widening of the grid lines and the decrease of battery efficiency. Summary of the invention

[0003] The technical solution adopted by the present invention to solve the above technical problems is to provide a conductive paste for solar cells, which can maintain the stability of its conductive silver paste, wherein the specific technical solution is:

[0004] A conductive paste for solar cells, comprising conductive metal powder, glass powder, and an organic carrier; wherein the organic carrier comprises a thermoplastic polymer, vinyl silicone oil, a polymerization inhibitor, other organic additives, and an organic solvent. The conductive paste is characterized in that the organic carrier contains vinyl silicone oil and a polymerization inhibitor.

[0005] Furthermore, the vinyl silicone oil refers to one or both of dimethyl silicone oil with a vinyl-terminated terminal group and vinyl-terminated polymethylvinylsiloxane, and the general structural formula is:

[0006]

[0007] Furthermore, the substituent R in the above general structural formula is any one or both of methyl and vinyl.

[0008] Furthermore, the viscosity of the vinyl silicone oil is 65mPa*S-50000mPa*S.

[0009] Furthermore, the content of the vinyl silicone oil is 0.05%-0.6%.

[0010] Furthermore, the polymerization inhibitor is one or more of 2,6-di-tert-butyl-4-methylphenol, hydroquinone, triphenylphosphine, and p-hydroxyanisole.

[0011] Furthermore, the mass ratio of the polymerization inhibitor to the vinyl silicone oil is 1:10-1:50.

[0012] Furthermore, the thermoplastic polymer is one or more of polyacrylic acid resin, polydimethylsilicone oil, polyvinyl butyral, ethyl cellulose, and cellulose acetate butyrate.

[0013] Furthermore, the other organic additives are one or more of dimethyl phthalate, dibutyl phthalate, dihexyl phthalate, dioctyl phthalate, dimethyl adipate, dibutyl adipate, silicone ether, polyamide wax, castor oil derivatives, and oxidized polyethylene wax.

[0014] Furthermore, the silicone ether in the other organic additives refers to a polyether-polysiloxane copolymer.

[0015] Furthermore, the silicone ether in the other organic additives refers to polyether polysiloxane copolymer. Further, the organic solvent is one or more of butyl carbitol, tripropylene glycol monomethyl ether, propylene glycol monomethyl ether, diethylene glycol butyl ether, terpineol, diethylene glycol butyl ether acetate, alcohol ester dodecahydrate, and alcohol ester hexadecene.

[0016] The ppm mentioned in the present invention refers to the mass concentration expressed as the mass of the solute in parts per million of the mass of the total solution. The parts per million concentration, the % mentioned above, and the percentage of each component are all mass concentrations.

[0017] In the present invention, the use of vinyl silicone oil as one of the formula components can make the conductive paste undergo polymerization reaction during the drying or sintering process, thereby inhibiting the collapse of the grid line due to the temperature increase during the drying or sintering process. At the same time, since the molecular weight of the vinyl silicone oil gradually increases during the polymerization reaction, it may also cause volume shrinkage. Therefore, the application of vinyl silicone oil can make the slurry have a narrower grid line width and a higher aspect ratio, thereby improving its short-circuit current and photovoltaic conversion efficiency. However, vinyl silicone oil is not stable at room temperature. Further, by introducing a polymerization inhibitor such as 2,6-di-tert-butyl-4-methylphenol into the slurry formula, the vinyl silicone oil can have better stability at room temperature. The present invention has the following beneficial effects relative to the prior art: by using vinyl silicone oil instead of traditional silicone oil and adding the polymerization inhibitor 2,6-di-tert-butyl-4-methylphenol, it can not only improve the photovoltaic conversion efficiency of the solar cell by increasing the aspect ratio of the grid line formed and reducing the fluctuation of the grid line, but also maintain the stability of the conductive silver paste. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a side view of the grid lines formed by screen printing, drying and sintering the slurry of Example 1.

[0019] Figure 2 This is a side view of the grid lines formed by the slurry of Example 2 through screen printing, drying and sintering.

[0020] Figure 3 This is a side view of the grid lines formed by screen printing, drying and sintering the slurry of Example 3.

[0021] Figure 4 This is a side view of the grid lines formed by screen printing, drying and sintering the slurry of Comparative Example 1. DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0023] Table 1 shows the fixed component contents in the examples and comparative examples, and Table 2 shows the differences in components in the examples and comparative examples based on the fixed components in Table 1. Table 2 also shows the viscosity values ​​of the silicone oils used in the examples and comparative examples.

[0024] The specific implementation is that the total amount of each embodiment and comparative example is 300 grams, the content of each component is according to the carrier and glass powder in the components in Table 1 and Table 2, and then the silver powder is added and stirred until it becomes a paste, and then it is repeatedly ground and dispersed with a three-roll mill to grind into a slurry with a fineness (FOG) of less than 10um.

[0025] Table 1 Content of fixed components of slurry in the formulations of the implementation and comparative examples

[0026]

[0027] The viscosity of each slurry at each rotation speed was measured using a Brookfield viscometer (purchased from BROOKFIELE VISCOMETER, model HBDV2T) with a No. 14 rotor 0.5 hours and 240 hours after sample preparation. The specific viscosity values ​​are shown in Table 3. From the viscosity measurement data after 0.5 hour of configuration, compared with Comparative Example 1, the viscosity of Example 1 is slightly reduced by replacing silicone oil with vinyl silicone oil. The contents of 2,6-di-tert-butyl-4-methylphenol added in Example 2 and Example 3 are 0.02% and 0.04% respectively. As the content of 2,6-di-tert-butyl-4-methylphenol increases, the viscosity of the slurry decreases. From the viscosity data of the slurry after 240 hours of configuration in Table 3, the viscosity of the slurry of Example 2, Implementation 3 and Comparative Example 1 is basically unchanged after 240 hours, but the rotation speed of the slurry of Example 1 at 50 rpm, 100 rpm and 200 rpm increases greatly after 240 hours, indicating that the slurries of Example 2, Implementation 3 and Comparative Example 1 are relatively stable, and since the slurry of Example 1 does not add the polymerization inhibitor 2,6-di-tert-butyl-4-methylphenol, the vinyl silicone oil in the slurry is likely to self-polymerize over time, causing the increase in the viscosity of the slurry.

[0028] Table 2 Differences in the content of slurry components in the examples and comparative examples

[0029]

[0030] Compared with Comparative Example 1, Example 4 uses 0.05% vinyl silicone oil instead of silicone oil, and adds 10ppm (0.001%) of polymerization inhibitor 2,6-di-tert-butyl-4-methylphenol. At this time, the ratio of vinyl silicone oil to 2,6-di-tert-butyl-4-methylphenol is 50:1. From the viscosity data, it can be seen that the viscosity of Example 4 changes little after 240 hours, indicating that the formula stability of Example 4 is also good.

[0031] Generally, the viscosity of the slurry at a rotation speed of 50 rpm is maintained in the range of 70-95 mPa*S to ensure printability. In Example 5 and Example 6, the viscosity of the vinyl silicone oil is adjusted from the original 1000 mPa*S to 65 mPa*S and 50000 mPa*S, respectively. By adjusting the amount of vinyl silicone oil used, Example 5 and Example 6 both achieve printability. At the same time, the viscosity changes little after 240 hours, indicating that the formula stability of Example 5 and Example 6 is also good.

[0032] One hour after the slurry was prepared, the slurries in Examples 1-3 and Comparative Example 1 were respectively printed on a P-type monocrystalline silicon wafer with a size of 159um*159um and a back silver paste and aluminum paste by screen printing, and the screen parameters used were 520 mesh, 17um wire diameter, 8um film thickness and 22um opening. The printed silicon wafer was heated in a multi-temperature zone tunnel furnace to obtain a stable solar cell, wherein the initial heating temperature of the tunnel furnace was 280°C and the final heating temperature was 900°C.

[0033] Table 3 Viscosity data of the slurry after 0.5 hour and 240 hours of preparation in the examples and comparative examples

[0034]

[0035] The line parameters were observed using a 3D microscope (purchased from Keyence, model VHX-970F), mainly measuring the line height and line width of the fine grid silver line printed on the solar cell, as well as the aspect ratio. Three cells were printed with each paste, and the line parameters at fixed positions on the cell were measured, and then the average value was taken. The specific line parameters are shown in Table 4.

[0036] From Table 4, it can be seen that compared with Comparative Example 1, the gate line width of the slurry in Example 1, Example 2 and Examples 4-6 through screen printing has been reduced to a certain extent, indicating that vinyl silicone oil can indeed play a role in narrowing the line width. Example 3 is based on Example 2, and the content of the polymerization inhibitor 2,6-di-tert-butyl-4-methylphenol is increased, and the ratio of the polymerization inhibitor to the vinyl silicone oil is changed from 1:20 to 1:10. It is found that with the increase of the polymerization inhibitor content, the gate line width is widened.

[0037] Table 4 Grid line parameters of solar cells prepared in the examples and comparative examples

[0038] Width(um) Height(um) Aspect Ratio Example 1 28.58 10.16 0.355 Example 2 29.88 10.04 0.336 Example 3 30.45 9.98 0.327 Example 4 29.97 10.03 0.335 Example 5 29.93 9.95 0.339 Example 6 29.90 10.08 0.337 Comparative Example 1 30.00 10.02 0.334

[0039] Ten solar cells were screen-printed from each slurry in Examples 1-4 and Comparative Example 1. The resulting solar cells were placed in a Berger solar cell tester under a standard light source condition (AM1.5G, 1000 mW / cm 2 ) were used to measure the open circuit voltage (Voc), short circuit current (Isc), fill factor (FF), efficiency (Eff), series resistance (Rs) and parallel resistance (Rsh). For 10 cells printed with each slurry, the average value of each cell performance parameter was taken after removing the abnormal value. The specific cell performance parameters are shown in Table 5. At the same time, a cell from each of Examples 1-4 and Comparative Example 1 was randomly selected, and the linear fluctuations in the side view of each cell were observed using a 3D microscope. Figure 1-Figure 4 .

[0040] The width and height of the grid lines formed by the slurry of Example 1 and Comparative Example 1 are compared. In Example 1, vinyl silicone oil is used instead of silicone oil in Comparative Example 1, which can shorten the width of the grid lines by 1.42um and increase the height by 0.14um, thereby improving the aspect ratio, resulting in an increase of 23.4mA in the short-circuit current of the solar cell produced, while the open circuit voltage and fill factor are improved, so that the photovoltaic conversion efficiency is improved by 0.115%. On the basis of Example 1, Example 2 and Example 3 introduce 2,6-di-tert-butyl-4-methylphenol. With the increase of the content of 2,6-di-tert-butyl-4-methylphenol, compared with Example 1, the width of the grid lines formed by Example 2 and Example 3 is increased, and the height of the grid lines is also reduced, resulting in a decrease in the current of the formed solar cell, but the open circuit voltage and fill factor are improved, so that the final photovoltaic conversion efficiency does not change much; Comparing the photovoltaic conversion efficiency in Examples 1-3 and Comparative Example 1, Examples 1-3 improve the photovoltaic conversion efficiency by 0.115%-0.118%.

[0041] Table 5 Photovoltaic performance parameters of solar cells made from the slurries in the examples and comparative examples

[0042]

[0043] It can be seen from the line side view that by comparing the line types printed in Example 1 with that printed in Comparative Example 1, the line type fluctuations in Example 1 printed by adding vinyl silicone oil instead of silicone oil are improved; when different contents of 2,6-di-tert-butyl-4-methylphenol are added to Example 1 to obtain Examples 2 and 3, it is found that the content of 2,6-di-tert-butyl-4-methylphenol is 0.02%, that is, Example 2 has a better printed line type, and the fluctuations are smaller than those in Example 1; when the content of 2,6-di-tert-butyl-4-methylphenol in Example 3 is 0.04%, the line type fluctuations are larger than those in Example 1.

[0044] In summary, using vinyl silicone oil instead of silicone oil in photovoltaic front silver paste can narrow the grid line width, thereby improving the short-circuit current and photovoltaic conversion efficiency of the solar cell. When the inhibitor 2,6-di-tert-butyl-4-methylphenol is further added on the basis of using vinyl silicone oil instead of silicone oil, the stability of the paste can be improved, and the photovoltaic conversion efficiency will not be reduced.

[0045] The specific embodiments of the present invention are described in detail above, but they are only examples, and the present invention is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions made to the present invention are also within the scope of the present invention. Therefore, the equalization changes and modifications made without departing from the spirit and scope of the present invention should be included in the scope of the present invention.

Claims

1. A conductive paste for solar cells, comprising conductive metal powder, glass powder, and an organic carrier; wherein: The organic carrier includes a thermoplastic polymer, vinyl silicone oil, a polymerization inhibitor, other organic additives, and an organic solvent; the conductive paste is characterized in that the organic carrier contains vinyl silicone oil and a polymerization inhibitor; The vinyl silicone oil refers to one or both of dimethyl silicone oil and vinyl-terminated polymethylvinylsiloxane with vinyl end groups, and the general structural formula is: Or R=CH3, CH=CH2; In the general structural formula of the vinyl silicone oil, the substituent R is any one or both of methyl and vinyl; The viscosity of the vinyl silicone oil is 65mPa*S-50000mPa*S; The content of the vinyl silicone oil is 0.05%-0.6%; The polymerization inhibitor is one or more of 2,6-di-tert-butyl-4-methylphenol, hydroquinone, triphenylphosphine, and p-hydroxyanisole; The mass ratio of the polymerization inhibitor to the vinyl silicone oil is 1:10-1:50; the thermoplastic polymer is one or more of polyacrylic acid resin, polydimethyl silicone oil, polyvinyl butyral, ethyl cellulose, and cellulose acetate butyrate; The other organic additives are one or more of dimethyl phthalate, dibutyl phthalate, dihexyl phthalate, dioctyl phthalate, dimethyl adipate, dibutyl adipate, silicone ether, polyamide wax, castor oil derivatives, and oxidized polyethylene wax; The silicone ether in the other organic additives refers to a polyether-polysiloxane copolymer; The organic solvent is one or more of butyl carbitol, tripropylene glycol monomethyl ether, propylene glycol monomethyl ether, diethylene glycol butyl ether, terpineol, diethylene glycol butyl ether acetate, alcohol ester dodecahydrate, and alcohol ester hexadecene.

Citation Information

Patent Citations

  • Solar cell sheet, assembly thereof, system and method of preparing solar cell sheet

    CN109301003A

  • Conductive silver paste for front surface of crystalline silicon solar cell and preparation method therefor and solar cell

    CN110663087A

  • Paste composition and solar cell element

    JP2011023598A